The Quality of Work Life and its Relationship to Contextual Performance in Light of the Modern Functions of Human Resources Management: Applied on the Employees of the Egyptian General Petroleum Corporation - Kashkousha, Najwa (The Arab Journal of Administration, 2022)
The study present deals with the dimensions of The Quality of Work life. The researcher focused on two dimensions: functional and organizational aspects, including ( participation in decision making, leadership style, stability and job security, training and development, education, work design and nature Work) The physical and moral working environment includes (The relationships within the career work, and the balance between personal and career life) and its relationship to the dimensions of contextual performance and the identification of the intermediate role of the modern functions of human resources management. The researcher focused on (Competency Framework for Succession Planning, and Competency Based Training) the purpose of the research to determine the nature and extent of the relationship between the dimensions of the concept of Quality of Work life and the dimensions of contextual performance in light of the modern functions of human resources management, and to arrive at a model that can predict the levels and nature of these relationships The problem of research was formed in the following What is the reality of applying the concept of Quality of Work life and its relationship to contextual performance in light of the modern functions of human resources management? The research methodology was descriptive analytical approach. The study was conducted on the same sample (322). First, the results showed that there is a direct relationship between the dimensions of the concept of The Quality of Work life as an independent variable and commitment to the dimensions of contextual performance as a variable for the employees in the companies in the field study. Second, there is a direct relationship between the dimensions of the concept of quality of life as an independent variable and modern functions of human resources management Thirdly, there is a positive relationship between the application of modern human resources management functions as an independent variable and the commitment to the dimensions of contextual performance as a variable for the employees of the companies, Fourth that the application of modern functions for the management of human resources and the intermediate role on the relationship between the dimensions of the concept of Quality of Work life and functional commitment to the dimensions of performance Contextual.